Modern approaches to the management of locally advanced cervical cancer - Raximova Xilolaxon (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
The management of locally advanced cervical cancer dictates a highly complex multidisciplinary intervention. This investigation provides an empirical analysis of modern therapeutic architectures, comparing conventional modalities against intensity-modulated radiation therapy (IMRT), image-guided adaptive brachytherapy (IGABT), and targeted immune checkpoint inhibition. Operating through a prospective observational design, the research evaluates 215 female patients (FIGO IB3-IVA) treated between 2021 and 2024. Statistical modeling reveals a profound clinical dichotomy. Cohorts managed with volumetric MRI-guided brachytherapy and concurrent chemotherapy achieved a 91.2% local control rate at 36 months, drastically outperforming the 74.5% success rate utilizing legacy two-dimensional point-based dosimetry. The analysis mathematically isolates a 60% decline in grade 3 or higher genitourinary and gastrointestinal adverse events when utilizing intensity-modulated fields. Theoretical exploration aligns these findings with the abscopal mechanics of neoantigen shedding, validating PD-1 blockade integration. The research advocates for the absolute obsolescence of two-dimensional radiotherapy, mandating volumetric adaptive brachytherapy and precision immunology to maximize long-term survivorship.